Carbon ion radiotherapy as definitive treatment in non-metastasized pancreatic cancer: study protocol of the prospective phase II PACK-study - Liermann, Jakob; Naumann, Patrick; Hommertgen, Adriane; Pohl, Moritz; Kieser, Meinhard; Debus, Jürgen; Herfarth, Klaus (BMC cancer, 2020)
Radiotherapy is known to improve local tumor control in locally advanced pancreatic cancer (LAPC), although there is a lack of convincing data on a potential overall survival benefit of chemoradiotherapy over chemotherapy alone. To improve efficacy of radiotherapy, new approaches need to be evolved. Carbon ion radiotherapy is supposed to be more effective than photon radiotherapy due to a higher relative biological effectiveness (RBE) and due to a steep dose-gradient making dose delivery highly conformal.
Gesehen am 10.11.2020